2020
DOI: 10.1113/jp280501
|View full text |Cite
|
Sign up to set email alerts
|

S100β‐mediated astroglial control of firing and input processing in layer 5 pyramidal neurons of the mouse visual cortex

Abstract: Inputs impinging on layer 5 pyramidal neurons perform essential operations as these cells represent one of the most important output carriers of the cerebral cortex. However, the contribution of astrocytes, a type of glial cell, to these operations is poorly documented. r Here we found that optogenetic activation of astrocytes in the vicinity of layer 5 in the mouse primary visual cortex induces spiking in local pyramidal neurons through Nav1.6 ion channels and prolongs the responses elicited in these neurons … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 136 publications
(369 reference statements)
2
31
0
Order By: Relevance
“…Coronal brainstem slices were obtained from 15-to 23-days old mice as previously described (Ryczko et al, 2020a). Briefly, mice were anesthetized with isoflurane (0.5-1 ml of isoflurane in a 1.5 L induction chamber) and decapitated with a guillotine.…”
Section: Patch-clamp Recordingsmentioning
confidence: 99%
“…Coronal brainstem slices were obtained from 15-to 23-days old mice as previously described (Ryczko et al, 2020a). Briefly, mice were anesthetized with isoflurane (0.5-1 ml of isoflurane in a 1.5 L induction chamber) and decapitated with a guillotine.…”
Section: Patch-clamp Recordingsmentioning
confidence: 99%
“…Recent studies have shown that exposure to extracellular S100B alters the firing properties of pacemaking neurons (Morquette et al, 2015;Ryczko et al, 2021). Based on these findings, we rationalized that any abnormal increase in extracellular S100B concentrations in the SNc could similarly alter DA neuron function.…”
Section: Th + and Thneurons From Primary Mouse Midbrain Cultures Showmentioning
confidence: 70%
“…Recent studies show that secreted S100B can buffer extracellular Ca 2+ , thereby altering the function of Ca 2+ sensitive K + channels in pacemaking neurons of the trigeminal ganglion and the cortex (Morquette et al, 2015;Ryczko et al, 2021). Given the precedence for a mechanism by which extracellular S100B can modulate neuronal function in multiple brain regions, we sought to determine the extent to which extracellular S100B exposure alters the activity of DA neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the wealth of literature available on how glia support neuronal functions, there are still substantial gaps in our understanding of how stimulated astrocytes regulate information processing of neurons at the cellular level. In a recent article published in The Journal of Physiology, Ryczko et al (2021) provide evidence that activation of astrocytes regulates the firing of layer 5 pyramidal neurons (L5PNs) by controlling extracellular Ca 2+ levels via releasing the Ca 2+ binding protein S100β.…”
mentioning
confidence: 99%